Antibacterial effects of Solanum tuberosum peel ethanol extract in vitro - Amanpour Raana; Abbasi-Maleki Saeid; Neyriz-Naghadehi Moslem; Asadi-Samani Majid (Shahrekord University of Medical Sciences, 2015)
Introduction: Today, medicinal plants are being widely used due to being natural, available, and cheaper than synthetic drugs and having minimum side effects. Since there were reports about the antibacterial properties of Solanum tuberosum (SE), the aim of this study was to investigate the antibacterial effects of SE ethanol extract in vitro condition on Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumoniae. Methods: Ethanol extract of SE peel was prepared by maceration method. Initially, antibacterial activity of ethanol extract of SE was qualitatively determined by disk diffusion test; then, the minimum inhibitory concentration and minimum bactericidal concentration were qualitatively determined by micro-dilution method. Results: SE peel extract had antibacterial properties and its effect was more pronounced on gram-positive bacteria, especially S. aureus (0.62±0.00 mg/ml). The extract had antibacterial activity on gram-negative bacteria, P. aeruginosa, too (8.33±2.88 mg/ml). Conclusion: SE peel extract has antibacterial activity and its effect on gram-positive bacteria was more pronounced than the investigated gram-negative bacteria. Therefore, it is suggested that SE peel constituent compounds be determined and to determine the exact mechanism of its antibacterial properties, and more comprehensive research be done to apply it, clinically.